Implementasi Metode Bercerita Interaktif untuk Mengembangkan Kemampuan Berbicara Pada Anak Usia Dini - Sari, Dian Mayang; Muthohar, Sofa; Mursid (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
Speaking ability is one of the important aspects in the physical and psychological development of early childhood. Therefore, children's speaking ability should be further developed from an early age. This study aims to determine the implementation of interactive storytelling methods to develop speaking ability in early childhood at RA Al Hidayah UIN Walisongo Semarang which consists of 16 children in class B1. This research uses qualitative descriptive methods. Data collection was done by observation, documentation and interview. The results of this study indicate that the implementation of interactive storytelling methods to develop children's speaking skills includes the pronunciation of sounds, language to express or convey thoughts, ideas or feelings orally. Before this method was applied, children tended to speak in less clear articulation. After the application of interactive storytelling method is applied, children are able to speak with clear articulation. Thus, the interactive storytelling method in developing children's speaking ability in class B1 at RA Al Hidayah UIN Walisongo Semarang proved to be successful in its implementation.